Single prolonged stress induces behavior and transcriptomic changes in the medial prefrontal cortex to increase susceptibility to anxiety-like behavior in rats - Iqbal, Javed; Huang, Geng-Di; Shen, Dan; Xue, Yan-Xue; Yang, Mei; Jia, Xiao-Jian (Frontiers in Psychiatry, 2024)
IntroductionTranscriptomic studies offer valuable insights into the pathophysiology of traumatic stress-induced neuropsychiatric disorders, including generalized anxiety disorder and post-traumatic stress disorder (PTSD). The medial prefrontal cortex (mPFC) has been implicated in emotion, cognitive function, and psychiatric disorders. Alterations in the function of mPFC have been observed in PTSD patients. However, the specific transcriptomic mechanisms governed by genes within the mPFC under traumatic stress remain elusive.MethodsIn this study, we conducted transcriptome-wide RNA-seq analysis in the prelimbic (PL) and infralimbic (IL) cortices. We employed the single prolonged stress (SPS) animal model to simulate anxiety-like behavior, which was assessed using the open field and elevated plus maze tests.ResultsWe identified sixty-two differentially expressed genes (DEGs) (FDR adjusted p < 0.05) with significant expression changes in the PL and IL mPFC. In the PL cortex, DEGs in the susceptible group exhibited reduced enrichment for cellular, biological, and molecular functions such as postsynaptic density proteins, glutamatergic synapses, synapse formation, transmembrane transport proteins, and actin cytoskeleton reorganization. In contrast, the IL-susceptible group displayed diminished enrichment for synapse formation, neuronal activity, dendrite development, axon regeneration, learning processes, and glucocorticoid receptor binding compared to control and insusceptible groups. DEGs in the PL-susceptible group were enriched for Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways related to Parkinson’s disease, Huntington's disease, Alzheimer's disease, and neurodegeneration processes. In the IL cortex, the susceptible group demonstrated enrichment for KEGG pathways involved in regulating stress signaling pathways and addiction-like behaviors, compared to control and insusceptible groups.ConclusionOur findings suggest that SPS activates distinct transcriptional and molecular pathways in PL and IL cortices of mPFC, enabling differential coping mechanisms in response to the effects of traumatic stress. The enhanced enrichment of identified KEGG pathways in the PL and IL mPFC may underlie the anxiety-like behavior observed in susceptible rats.